THE EFFECT OF CIVIC EDUCATION BASED VCT ANALYSIS VALUE MORAL DILEMMAS ON GLOBAL INSIGHTS CITIZENS COMPETENCES - Dadang Sundawa, Syifa Siti Aulia, Aim Abdulkarim, (Jurnal Civicus, 2015)
Civic education conventional method ignore the monotonous process of building value in facing of globalization. VCT analysis moral dilemmas method used one of the learning strategies to form a global insights citizens competences. This study developed about what a significant different the attitude, skill, and knowledge of global insights citizens competences between the class student who useÂ  VCT analysis moral dilemmas in civic education with donâ€™t use VCT analysis moral dilemmas. The method in studies used quantitative approach with quasi experimental study. Based on different test performed, so that the value analysis dilemmas moral han an influence on global insights citizens competences.